Influences of pre-precipitated δ phase on microstructures and hot compressive deformation features of a nickel-based superalloy. (March 2019) - He, Dao-Guang; Lin, Y.C.; Wang, Li-Hua; Wu, Qiao; Zu, Zi-Heng; Cheng, Hao
Abstract: Microstructural changes and flow characteristics of a nickel-based superalloy with pre-precipitated δ phases (Ni3 Nb) are investigated using hot compressive experiments. The higher forming temperature or lower strain rate not only aggravate the arrangement/annihilation of dislocations, but also stimulate the generation/growth of substructures and dynamic recrystallization (DRX) grains. As the percentage of pre-precipitated δ phases is raised, the obvious work hardening behavior induced by the intense interactions between δ phases, grain boundaries and substructures occurs in the initial hot forming process. While the alloy is further strained, the DRX behavior are obviously promoted by δ phases. Considering the influences of pre-precipitated δ phases and forming parameters, an improved Hensel-Spittel-Carofalo (HSC) equation and an e -insensitive support vector regression (e-SVR) model are developed for reconstructing the flow features of the researched alloy. The minor deviations between the tested and forecasted true stresses indicate that the developed HSC model and e -SVR model can be properly utilized to characterize the hot forming features of the researched superalloy with different percentages of pre-precipitated δ phases. Highlights: Hot forming behaviors of a nickel-base alloy with different pre-precipitated δ phase (Ni3Nb) are investigated. Effects of forming parameters and δ phase on flow features and microstructural variations are significant. Evolution of substructures is weaken at higher strain rate, while becomes obvious at higher forming temperature. The increased pre-precipitated δ phase can aggravate the nucleation of substructures and DRX grains. Flow features with pre-precipitated δ phase can be precisely reconstructed by HSC and e -SVR models